Role of Computed Tomography Scan Chest for Management of COVID-19 - Zeeshan Jamal, Naimatullah Bozdar, Din Muhammad Sohu, Inayatullah, Akhtar Hussain Phul, Rabia Hafeez (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the role of chest computed tomography for management of Covid-19. Study design: Prospective study Place and duration of study: Department of Radiology, Peoples University of Medical & Health Sciences for Women, Nawabshah, Shaheed Benazirabad from 1st August 2020 to 30th September 2021. Methodology: Two hundred patients were enrolled within the age range of 18-70 years. The clinical/medical record of all those patients who were moderately to critically ill assessed in detail. These patients visited the hospital with symptoms of cough, fever, hypoxia, dyspnea, diarrhoea, flu, headache and other related symptoms. All patients underwent chest reverse transcription polymerase chain reaction as well as chest computed tomography scan. The reverse transcription polymerase chain reaction was performed through nasopharyngeal swab. Results: The mean age of the patients was 64.5±5.6 years with 120 (60%) males and 80 (40%) females. The specificity was 75%, sensitivity 100%, positive predictive value 79%, negative predictive value 66.67% and diagnostic accuracy 75%. Conclusion: Computed tomography scan imaging is a most reliable with high sensitivity and non-predictive value